The ecological component of agrotourism development under the COVID-19 pandemic - Oleksenko, Roman; Bilohur, Stanislav; Rybalchenko, Nina; Verkhovod, Iryna; Harbar, Halina (Political Questions, 2021)
The study was conducted to identify the environmental component in the development of agrotourism and its impact on the psychological state of society in theCOVID-19 pandemic.The experience of European countries shows the environmental, economic, and social benefits of agrotourism. The methodological basis of the study is the general scientific methods of cognition and social processes (analysis, synthesis, generalization, classification) togetherwithsociological methods of obtaining empirical data. The National Tourism Organization of Ukraine has declared 2020 as the year of green rural tourism, an important component from which agrotourism arises. It is concluded that, la peculiarity of the development of agrotourism in Ukraine at the current stage is the acquisition of innovative forms of organization according to the growing needs of consumers, the efficient use of the natural, ecological, socioeconomic, and historical-cultural potential of the territory and the achievement of the required level of profitability. The situation of crisis and instability is accompanied by the presence of uncertainty associated with the COVID-19 pandemic; the need to form the concept of tourism development 4.0; introduction of ICT and development of innovative technologies in agrotourism in rural areas; training of professionals in the field of agrotourism.